Tuning the charge stabilization and transport in naphthalimide-based semiconductors via a fused-ring and core-engineering strategy - González-Núñez, Raúl; Alonso-Navarro, Matías J.; Suarez-Blas, Fátima; Gala, Elena; Ramos, M. Mar; Segura, José L.; Ponce-Ortiz, Rocío (My University, 2024)
The synthesis and characterization of a family of rationally designed compounds based on naphtha- limide units attached, through conjugated nitrogenated linkers (i.e. pyrazine and imidazoline units), to fused thiophene-based moieties is shown. This combination of different donor–acceptor moieties allows fine tuning of the HOMO and LUMO energy levels, and thus the modulation of their electronic properties. A comprehensive physical chemistry study is carried out, in which the nature of the neutral and charged species are analyzed and their electrical performance is understood in terms of molecular and supramolecular characteristics.
Keywords: Semiconductores; Charge stabilization; Fused-ring; Core-engineering; Naphthalimide-based semiconductors